Association between metabolic phenotypes and incident pre-sarcopenia: 3 years follow-up of Tehran Lipid and Glucose Study - Behnaz Abiri; Amirhossein Ramezani Ahmadi; Ali Valizadeh; Zahra Seifi; Farhad Hosseinpanah; Fereidoun Azizi; Majid Valizadeh (BMC, 2024)
Abstract Objectives In the context of musculoskeletal health, the emergence of pre-sarcopenia as a precursor to sarcopenia has garnered attention for its potential insights into early muscle loss. We explored the association between different metabolic phenotypes of obesity, and the incidence of pre-sarcopenia over a 3-year follow-up in a cohort from the Tehran Lipid and Glucose Study (TLGS). Methods In this 3-year longitudinal study, 2257 participants were categorized into four groups based on their BMI and metabolic status: metabolically healthy normal weight (MHNW), metabolically healthy overweight/obese (MHO), metabolically unhealthy normal weight (MUNW), and metabolically unhealthy overweight/obese (MUO). The participants were assessed for various anthropometric and body composition indices including muscle mass determined by bioelectrical impedance analysis (BIA). Blood samples were collected for metabolic indices, and participants underwent measurements for blood pressure. Pre-sarcopenia was defined based on low muscle mass. Statistical analyses included logistic regression and chi-squared tests. Results The MUNW group exhibited the highest prevalence of pre-sarcopenia (33.5%), while the MHO group had the lowest (2.8%). Adjusted models revealed that the odds ratio for pre-sarcopenia was higher in the MUNW group (OR = 2.23, P < 0.001), whereas the MHO and MUO groups showed lower odds (OR = 0.11 and 0.13, both P < 0.001). Notably, the association was gender-dependent, with MUNW females having a higher risk even after adjustments (OR = 2.37, P = 0.042). Conclusion Our findings suggest that metabolic health may play a pivotal role in pre-sarcopenia, emphasizing the need for targeted interventions based on both metabolic and obesity phenotypes.